The new ASEAN in Asia Pacific and beyond - Narine, Shaun 1966- (Boulder, Colorado Lynne Rienner Publishers, Inc., 2018)
"Traces ASEAN's political and economic development and explores its impact both within Southeast Asia and beyond"--Provided by publisher.
ASEAN in the twenty-first century -- History : from creation to crisis -- The postcrisis reform -- Regional institutionalism -- Relations with China -- Relations with the United States -- ASEAN and the regional powers -- ASEAN's role in Asia Pacific.
Includes bibliographical references (pages 281-299) and index.
Keywords: ASEAN; Southeast Asia -- Foreign relations